"...Our support is not enough": a qualitative analysis of recommendations from informal caregivers of women with female genital fistula in Uganda - Ashley Mitchell; Hadija Nalubwama; Justus K. Barageine; Suellen Miller; Abner P. Korn; Josaphat Byamugisha; Susan Obore; Alison M. El Ayadi (Inishmore Laser Scientific Publishing Ltd, 2023)
Informal caregivers remain critical across the care continuum for complex and stigmatized conditions including female genital fistula, particularly in lower-resource settings burdened by underfunded health systems and workforce shortages. These caregivers often provide significant nonmedical support in both community and facility settings, without pay. Despite their unique insight into the lived experiences of their patients, few studies center the perspectives of informal caregivers. We asked informal caregivers of women seeking surgical treatment of fistula in Kampala Uganda for their ideas about what would improve the recovery and reintegration experiences of their patients. Economic empowerment and community capacity building emerged as primary themes among their responses, and they perceived opportunities for clinical medicine and global health to strengthen strategies for fistula prevention through reintegration. Informal caregivers urged simultaneous investment in women's economic status and community capacity to build fistula-related awareness, knowledge, and skills to improve inclusion of both fistula patients and their informal caregivers.